VISIBLE SPECTROPHOTOMETRIC METHOD DEVELOPMENT AND VALIDATION OF IMATINIB IN BULK AND FORMULATION - KUMBHAR, SMITA; MATOLE, VINOD; THORAT, YOGESH; SHEGAONKAR, ANITA; HOSMANI, AVINASH (International Journal of Current Pharmaceutical Research, 2020)
Objective: A new, simple, sensitive, precise and reproducible UV visible spectrophotometric method was developed for the determination of Imatinib in pharmaceutical formulations with alizarin. Methods: The method is based on formation of yellow-colored complex. The UV spectrum of Imatinib in methanol showed λ max at 431 nm. Beer’s law is valid in the concentration range of 10-70 μg/ml. This method was validated for linearity, accuracy, precision, ruggedness and robustness. Results: The method has demonstrated excellent linearity over the range of 10-70 μg/ml with regression equation y =0.013x-0.017 and regression correlation coefficient r2= 0.997. Moreover, the method was found to be highly sensitive with LOD (4.3μg/ml) and LOQ (13.07μg/ml). Conclusion: Based on results the proposed method can be successfully applied for the assay of Imatinib in various pharmaceutical dosage forms.